2015
DOI: 10.12716/1001.09.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Probability of Ship on Collision Courses Based on the New PAW Using MMG Model and AIS Data

Abstract: This paper proposes an estimation method for ships on collision courses taking crash astern maneuvers based on a new potential area of water (PAW) for maneuvering. A crash astern maneuver is an emergency option a ship can take when exposed to the risk of a collision with other ships that have lost control. However, lateral forces and yaw moments exerted by the reversing propeller, as well as the uncertainty of the initial speed and initial yaw rate, will move the ship out of the intended stopping position land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Modeling and simulation are crucial in safety research; correspondingly, most of the publications found starting in 2007 until 2016 model the probability of grounding and collision in specific waters, such as the Gulf of Finland, and Madura strait (Asmara et al 2015), and use algorithmic approaches to determine the areas of higher collision risks (Xiang et al 2013). AIS data have been used to demonstrate, for example, that avoidance maneuvers are operated too late or that (in some cases) the intensity of traffic does not alone increase the probability of grounding.…”
Section: Collision and Grounding Risk Assessmentmentioning
confidence: 99%
“…Modeling and simulation are crucial in safety research; correspondingly, most of the publications found starting in 2007 until 2016 model the probability of grounding and collision in specific waters, such as the Gulf of Finland, and Madura strait (Asmara et al 2015), and use algorithmic approaches to determine the areas of higher collision risks (Xiang et al 2013). AIS data have been used to demonstrate, for example, that avoidance maneuvers are operated too late or that (in some cases) the intensity of traffic does not alone increase the probability of grounding.…”
Section: Collision and Grounding Risk Assessmentmentioning
confidence: 99%
“…AIS data utilization to be used for conducting a risk assessment for subsea facilities in Madura Strait is done by Mulyadi et.al by defining the safe distance of dropping anchor of the ship [3]. AIS historical data based on around area Tanjung Perak Surabaya harbor has used to analyze the probability of collision course ship when is maneuvering in ship trajectory [4].…”
Section: Introductionmentioning
confidence: 99%